How to promote residents' collaboration in destination governance: A framework of destination internal marketing. (June 2022) - Zhang, Tong; Chen, Ye; Wei, Mingqiu; Dai, Meiling
Abstract: Mobilizing residents' collaboration in destination governance has become imperative for local governments to achieve the success and sustainability of a destination. However, few studies have explored residents' collaboration from the perspective of governance strategies and instruments. Based on a case study of Hangzhou, China, this paper adopts the grounded theory method to inductively construct a new destination governance framework of destination internal marketing to promote residents' collaboration. The findings reveal: (1) In the framework of destination internal marketing, residents are regarded as critical collaborators, playing the roles of achievement sharers, power holders, and responsibility undertakers. (2) Six governance instruments—supply optimization, substitutive compensation, constructing participation systems, participation supports, sharing field creation, and value communication are utilized for mobilizing residents' collaboration. (3) Through destination internal marketing, a government–resident collaborative relationship based on mutual trust, equal status, and shared goals could be developed. The findings have theoretical and practical significance for effective governance in destinations. Highlights: Residents are critical collaborators in destination governance. A new governance framework of destination internal marketing is developed. Six governance instruments for promoting residents' collaboration are identified. A more effective government–resident collaborative relationship is proposed.